OPTIMASI PROSES PRODUKSI PLASTIK PENYIMPANAN MAKANAN DI PT SANIPAK INDONESIA - Panniarti Lubis, Dewi; Elsya Paskaria Loyda Tarigan (Computer Science and Industrial Engineering, 2024)
Optimizing the production process is an activity carried out by production to increase efficiency, productivity and quality of each product produced. This activity is carried out by preventing the occurrence of several factors, one of which is waste in each process flow. The impact of waste that occurs on the production process flow is in the form of a decrease in the quality of the product being worked on. PT Sanipak Indonesia is a company engaged in the plastic manufacturing industry. One of them is food storage plastic, this company uses a Make to Order system. Food storage plastic production at PT Sanipak Indonesia experienced problems with product quality decreasing by up to 15% from the previous month. This results in many defective and wasted products in the storage warehouse, so that optimizing the production process does not run smoothly. The accumulation of defective products due to the production process that has been carried out causes losses for the company. Many products do not achieve good quality, this factor also occurs due to the minimal placement area for products that have been processed. Because production did not reach the desired quality target, overall improvements were made from the start to the end of the process. This research aims to find out how to reduce the waste that occurs so that the production process can run optimally. This research uses an analytical method based on the lean manufacturing approach with value stream mapping. To analyze waste, this research uses a fishbone diagram. The results obtained from periodic inspections carried out for 6 days were the occurrence of waste overproduction with the highest level of waste with a weight of 51.02%, and the lowest waste defect with a weight of 48.98%. This problem can be solved in several ways, one of which is repairing waste defects and waste overproduction by regularly calibrating machines or work tools according to SOPs, as well as replacing machines that are no longer suitable for reuse, and expanding storage warehouses by providing labels. product indication in each storage area. Based on the results of the Future State Mapping mapping carried out, a Process cycle efficiency value of 79.80% was obtained from 68.37%. These results showed that production had increased by 18.2%, which enabled the production process to optimize the production process again, so that the quality of the products produced increased again.